The Use of MPSS for Whole-Genome Transcriptional Analysis in Arabidopsis - Meyers, Blake C.; Tej, Shivakundan Singh; Vu, Tam H.; Haudenschild, Christian D.; Agrawal, Vikas; Edberg, Steve B.; Ghazal, Hassan; Decola, Shannon (Genome Research, 2004)
We have generated 36,991,173 17-base sequence “signatures” representing transcripts from the model plant Arabidopsis. These data were derived by massively parallel signature sequencing (MPSS) from 14 libraries and comprised 268,132 distinct sequences. Comparable data were also obtained with 20-base signatures. We developed a method for handling these data and for comparing these signatures to the annotated Arabidopsis genome. As part of this procedure, 858,019 potential or “genomic” signatures were extracted from the Arabidopsis genome and classified based on the position and orientation of the signatures relative to annotated genes. A comparison of genomic and expressed signatures matched 67,735 signatures predicted to be derived from distinct transcripts and expressed at significant levels. Expressed signatures were derived from the sense strand of at least 19,088 of 29,084 annotated genes. A comparison of the genomic and expression signatures demonstrated that ∼7.7% of genomic signatures were underrepresented in the expression data. These genomic signatures contained one of 20 four-base words that were consistently associated with reduced MPSS abundances. More than 89% of the sum of the expressed signature abundances matched the Arabidopsis genome, and many of the unmatched signatures found in high abundances were predicted to match to previously uncharacterized transcripts.
10.1101/gr.2275604